Hsa_circ_0000119 promoted ovarian cancer development via enhancing the methylation of CDH13 by sponging miR‐142‐5p. Issue 3 (8th December 2022) - Ma, Guiyan; Li, Yan; Meng, Fandong; Sui, Chengguang; Wang, Yang; Cheng, Dali
Abstract: Ovarian cancer is the leading cause of gynecological cancer‐related death in women, and is difficult to treat. The aim of our study is to explore the role and action mechanism of hsa_circ_0000119 in ovarian cancer, thus to analyze whether the circular RNA is a potential target for the treatment of the disease. In this present study, our data shows that hsa_circ_0000119 and DNA methyltransferase 1 (DNMT1) was increased, while miR‐142‐5p was decreased in ovarian cancer. Overexpression of hsa_circ_0000119 promoted tumor growth, while silencing of hsa_circ_0000119 resulted in an opposite effects. Decreasing of hsa_circ_0000119 also notably inhibited the proliferation, migration, and invasion of the ovarian cancer cells. Moreover, the data proves that hsa_circ_0000119 negatively regulated miR‐142‐5p and cadherin 13 (CDH13) expression, but positively regulated DNMT1 expression. miR‐142‐5p could interact with hsa_circ_0000119 and DNMT1 3′‐UTR. Silencing of DNMT1 could reverse the inhibition of hsa_circ_0000119 to miR‐142‐5p and CDH13 expression. Importantly, higher level of CDH13 promoter methylation existed in the ovarian tumors than that in matched normal tissues. DNA methyltransferase inhibitor could increase the expression of CDH13 in ovarian cancer cells. In addition, our results also prove that increasing of CDH13 or miR‐142‐5p effectively reversed the inhibition of hsa _circ_0000119 to the cell malignant phenotypes. Overall, our data demonstrate that hsa_circ_0000119 facilitated ovarian cancer development through increasing CDH13 expression via promoting DNMT1 expression by sponging miR‐142‐5p. Our data demonstrate the potential role of hsa_circ_0000119 in the treatment of ovarian cancer.